Management Factors Associated with Sow Reproductive Performance After Weaning. Issue 3 (10th October 2012) - de, E; Laanen, M; Dewulf, J; Jourquin, J; de, A; Maes, D
Contents To achieve optimal reproductive performance in pig herds, sows need to become pregnant as soon as possible after weaning. The aim of this study was to investigate herd and management factors associated with reproductive performance of sows after weaning. A questionnaire pertaining to sow management at weaning and herd reproductive data were collected from 76 randomly selected commercial pig herds in Belgium. Associations between the herd factors and two reproductive parameters after weaning (weaning‐to‐oestrous interval: WEI and percentage of repeat breeders: RB) were analysed using general linear mixed models. A separated feeding strategy of breeding gilts from 60 kg onwards was significantly associated with a shorter WEI (5.54 vs 7.28 days; p = 0.040). Factors significantly associated with a lower percentage of RB were housing the newly weaned sows separated from the gestating sows (7% vs 12%; p = 0.003), using semen < 4 days after collection (7–9 vs 14%; p = 0.014) and stimulating oestrus twice a day (8 vs 11%; p = 0.025). In conclusion, some management practices, such as feeding strategy of breeding gilts, housing conditions of sows, method of oestrous stimulation and storage duration of semen, have an influence on the outcome of reproductive parameters such as weaning‐to‐oestrous interval and percentage of repeat breeders. These practices can be implemented rather easily by pig producers and may consequently lead to improvements of reproductive performance of sows after weaning.